2018
DOI: 10.1007/s12022-018-9518-7
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Extranodal Extension in Papillary Thyroid Cancer Based on the Size of the Metastatic Node: Adverse Histologic Features Are Not Limited to Larger Lymph Nodes

Abstract: Extranodal extension (ENE) is a prognostic indicator of aggressiveness for papillary thyroid cancer (PTC). The association between the size of metastatic nodes and the prevalence of ENE has not been previously explored. However, there is a common belief that small lymph nodes with metastatic disease do not significantly impact patient outcome. This study investigates the relationship between the prevalence of ENE and the size of a positive lymph node. Linear dimensions and malignant histological characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Macroscopic ENE was found in 10.4% of PTC patients, and lung metastasis was found in 2.3% of patients. Macroscopic ENE and lung metastasis rates were similar to the published literature [9][10][11]4]. After multivariate logistic regression analysis, macroscopic ENE, macroscopic ETE and number of positive nodes showed association with lung metastasis, which indicated the independent predictive value.…”
Section: Discussionsupporting
confidence: 85%
“…Macroscopic ENE was found in 10.4% of PTC patients, and lung metastasis was found in 2.3% of patients. Macroscopic ENE and lung metastasis rates were similar to the published literature [9][10][11]4]. After multivariate logistic regression analysis, macroscopic ENE, macroscopic ETE and number of positive nodes showed association with lung metastasis, which indicated the independent predictive value.…”
Section: Discussionsupporting
confidence: 85%
“…Roh et al [4] found that sex, ETE, N1 classi cation, and number of positive nodes were all signi cant factors associated with occurrence of ENE. Other studies have demonstrated that large tumor size [22] and lymph node size [23] increase the risk of ENE for metastatic PTC.…”
Section: Discussionmentioning
confidence: 96%
“…Second, the average follow-up time was 7.4 years (89 months), which may be shorter than recurrence time for PTMC. Third, in addition to the number and diameter of metastatic lymph nodes, extranodal extension has been identified as prognostic factor for thyroid cancer (40). However, extranodal extension was not mandated in the pathologic report before 2013 in our hospital, which may generate some bias in our study.…”
Section: Discussionmentioning
confidence: 99%